Unraveling cell wall polysaccharides during blueberry ripening: insights into the roles of rhamnogalacturonan-I and arabinogalactan proteins in fruit firmness - Sanhueza, Dayan; Balic-Norambuena, Iván; Sepúlveda-Orellana, Pablo; Siña-López, Sebastián; Moreno, Adrián A.; Moya-León, María Alejandra; Saez-Aguayo, Susana (Frontiers in Plant Science, 2024)
Blueberries (Vaccinium corymbosum) undergo significant texture changes during development and ripening, notably a consistent decrease in firmness, which affects fruit quality, consumer preference, transportability, and shelf life. This study examined the composition and structural modifications of the cell wall in five commercially available 2 blueberry varieties with differing firmness levels at harvest. Our approach integrated various biochemical techniques for a comprehensive analysis of cell wall components to elucidate firmness differences at the harvest stage. One of the conclusions was the relationship between a low degree of pectin methylesterification and the presence of increased egg-box structures, which correlated with increased firmness. The data suggests that minor domains such as rhamnogalacturonan-I participate in firmness modulation through their side branches or by linking to arabinogalactan proteins. Additionally, the xyloglucan structure can be one of the determinants of fruit firmness. Although, this work provides, a broad insight into the relationship between cell wall composition and firmness in blueberry, a more detailed analysis, specifically focusing on pectin and hemicelluloses, would be of significant value.